The Effect of Altruism on the Performance of Kassi-Kassi Health Center Employees in 2023 - St. Nurchaliza Damayanti Pratiwi; Suharni A. Fachrin; Arni Rizqiani Rusydi; Arman Arman; Nurmiati Muchlis; Reza Aril Ahri (Jurnal EduHealth, 2023)
The performance of employees serves as an indicator of their ability to make meaningful contributions to the organization's goals and objectives. Aims of the research to find out the influence of Altruism on the performance of Kassi-Kassi Health Center employees. The population of this study was all employees of the Kassi-Kassi Health Center in Makassar City. Data analysis using Statistical Product and Service Solutions(SPSS). Results: most of the respondents graduated from tertiary institutions, were female, had civil servant status, and had worked for ≥ 5 years. There was a significant positive effect of altruism on the performance of Kassi-Kassi Health Center staff (p<0.05). Conclusion: There is an influence of Organizational Citizenship Behavior (OCB) on the Performance of Kassi-Kassi Health Center in Makassar City